Provenance of the Lower Triassic Clastic Rocks in the Southwestern Margin of the South China Craton and Its Implications for the Subduction Polarity of the Paleo-Tethyan Ocean - Han, Chao; Huang, Hu; Yang, Chenchen; Wang, Linxi; Luo, Hongwei (Frontiers in Earth Science, 2022)
The southwestern margin of the South China Craton preserves a Late Permian to Early Triassic sedimentary succession, the provenance of which helps to constrain the magmatic history and tectonic evolution of the Paleo-Tethyan Orogen. In this study, we present new detrital zircon U-Pb age, trace element, Hf isotope, and whole-rock geochemical composition analyses from the Lower Triassic Qingtianbao Formation, to distinguish the provenance of clastic rocks. The results show that the detrital zircons of the Qingtianbao Formation are characterized by age spectrum of unimodal, with the age peak of ~ 260 Ma and have a geochemical affinity to within-plate sources. Most of these zircons have positive εHf(t) values (+1.6 to +5.9), similar to those of Emeishan rhyolites. The whole-rock geochemistry of most clastic samples shows no Nb-Ta anomalies on primitive mantle-normalized elemental diagrams. These features imply a source related to Emeishan volcanic rocks. Integration of the geologic and provenance records in the southwestern margin of the South China Craton, we suggest that the Paleo-Tethyan Ocean may undergo a unidirectional subduction westward beneath the Indochina Block during the Late Permian-Early Triassic.